2017
DOI: 10.1038/s41598-017-17126-2
|View full text |Cite
|
Sign up to set email alerts
|

Cdc7-Dbf4-mediated phosphorylation of HSP90-S164 stabilizes HSP90-HCLK2-MRN complex to enhance ATR/ATM signaling that overcomes replication stress in cancer

Abstract: Cdc7-Dbf4 kinase plays a key role in the initiation of DNA replication and contributes to the replication stress in cancer. The activity of human Cdc7-Dbf4 kinase remains active and acts as an effector of checkpoint under replication stress. However, the downstream targets of Cdc7-Dbf4 contributed to checkpoint regulation and replication stress-support function in cancer are not fully identified. In this work, we showed that aberrant Cdc7-Dbf4 induces DNA lesions that activate ATM/ATR-mediated checkpoint and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…CDC7 has already been reported to influence MRE11 activity through phosphorylation of the HSP90 chaperone, thus stabilizing a ATR–HSP90–HCLK2–MRE11 complex . Based on our data, it is tempting to speculate that CDC7 may regulate MRE11‐dependent processes through direct phosphorylation, promoting MRE11 nuclease activity and, in the long range, its retention at replication factories.…”
Section: Discussionsupporting
confidence: 58%
“…CDC7 has already been reported to influence MRE11 activity through phosphorylation of the HSP90 chaperone, thus stabilizing a ATR–HSP90–HCLK2–MRE11 complex . Based on our data, it is tempting to speculate that CDC7 may regulate MRE11‐dependent processes through direct phosphorylation, promoting MRE11 nuclease activity and, in the long range, its retention at replication factories.…”
Section: Discussionsupporting
confidence: 58%
“…4 ). Since Cdc7-Dbf4 interacts with and phosphorylates HSP90-MRN complex to enhance ATR/ATM checkpoint signaling and DNA damage tolerance for the survival of cancer cells [ 41 ], the kinase inhibitor becomes an excellent anti-cancer agent that not only blocks DNA synthesis at the beginning but also sensitizes cancer cells to DNA damage agents. Although the resistance development of chemo- and radio-therapy, cis-diamminedichloroplatinum (II) (CDDP, cisplatin) and radiation are still widely used for the treatment of various solid tumors, including oral cancers [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may reflect an overlapping regulatory function between Cdc7 and ATM/ATR in replication fork machinery under replication stress. Certain studies [ 45 47 ] also confirm this phenomenon. Furthermore, Montagnoli et al demonstrated that MCM2 phosphorylation at Ser-41 (putative CDK-dependent site) and Ser-139 (putative CK2-dependent site) were not affected by reducing Cdc7 [ 24 ].…”
Section: Phosphorylation Of Mcms By Cdc7mentioning
confidence: 63%